Romy and Michele's high school reunion [videorecording (DVD)] - Sorvino, Mira; Kudrow, Lisa; Garofalo, Janeane (Touchstone Home Video : Distributed by Buena Vista Home Video, 1999)
Two women get into trouble when they go to their high school reunion and lie about their lives after twelfth grade.